Culture's Consequences: Comparing Values, Behaviors, Institutions and Organizations Across Nations - Geert Hofstede (USA Sage Publications, 2001)
Geert Hofstede has completely rewritten, revised and updated Culture's Consequences for the twenty-first century, he has broadened the book's cross-disciplinary appeal, expanded the coverage of countries examined from 40 to more than 50, reformulated his arguments and a large amount of new literature has been included. The book is structured around five major dimensions: power distance; uncertainty avoidance; individualism versus collectivism; masculinity versus femininity; and long term versus short-term orientation.
Keywords: Cross-cultural studies; National characteristics; Ethnopsychology; Nonfiction; Cultural; Psychology; Business; Sociology; Anthropology; Science; Academic; Politics; Cultural studies; International Business and Management (ECO2023-N )